Software Related To Rough Set Theory - Mehta, P; Jain, P (International Journal of Computer Sciences and Engineering, 2025)
The Rough Set Theory is used for incomplete or imperfect knowledge by using the lower and upper approximation. To perusal the data set using Rough Set Theory, many softwares are available. The present paper deals about the softwares which are predominantly utilized for Rough Set Theory in exploring the information system